PEMANFAATAN ARTIFICIAL INTELLIGENCE MELALUI APLIKASI GAMMA.AI DALAM PEMBELAJARAN FIQIH MATERI IBADAH DI SMK PEMUDA KRIAN - Tiara Wiritanaya; Anita Puji Astutik (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
The tendency of student boredom due to the dominance of conventional lecture methods and the demands of adapting dynamic religious materials in the digital era are the background of this research. These obstacles trigger the need to utilize intelligent instruments to simplify complex religious texts for Generation Z. The focus of this research is to describe the use of Artificial Intelligence (AI) through the Gamma.ai application in learning Islamic Jurisprudence (Fiqh Ibadah) on Zakat at Pemuda Krian Vocational School and analyze its impact on the understanding and activeness of 10th grade students. The research steps were carried out using a qualitative approach with a case study method, where actual data collection was obtained through observation techniques, semi-structured interviews, and documentation. The research findings show that Gamma.ai successfully reduces the administrative burden of teachers in designing teaching materials, while being able to concretize the details of contemporary zakat mal through automatic infographic visualization. Based on the principle of dual coding, the combination of AI visualization and teacher navigation empirically boosts cognitive retention and triggers student participatory activity in conducting cross-sector discussions. The main conclusion confirms that the integration of Gamma.ai has proven effective in creating a modern, efficient, and adaptive Islamic Religious Education learning ecosystem without neglecting the authenticity of the substance of Islamic law. Educators are recommended to optimize their ability to formulate instructions (prompts) precisely in order to maintain the accuracy of the interpretation of religious law. ABSTRAK Kecenderungan kejenuhan siswa akibat dominasi metode ceramah konvensional serta tuntutan penyesuaian materi keagamaan yang dinamis di era digital melatarbelakangi penelitian ini. Hambatan tersebut memicu perlunya pemanfaatan instrumen cerdas guna menyederhanakan materi teks keagamaan yang kompleks bagi generasi Z. Fokus penelitian ini adalah mendeskripsikan pemanfaatan Artificial Intelligence (AI) melalui aplikasi Gamma.ai dalam pembelajaran Fikih Ibadah materi Zakat di SMK Pemuda Krian serta menganalisis dampaknya bagi pemahaman dan keaktifan siswa kelas X. Langkah-langkah penelitian dijalankan menggunakan pendekatan kualitatif dengan metode studi kasus, di mana pengumpulan data aktual diperoleh lewat teknik observasi, wawancara semi-terstruktur, dan dokumentasi. Temuan riset menunjukkan bahwa Gamma.ai berhasil mereduksi beban administratif guru dalam mendesain bahan ajar, sekaligus mampu mengonkretkan rincian zakat mal kontemporer melalui visualisasi infografis otomatis. Berdasarkan prinsip dual coding, perpaduan visualisasi AI dan navigasi guru ini secara empiris mendongkrak retensi kognitif serta memicu keaktifan partisipatif siswa dalam melangsungkan diskusi lintas sektor. Simpulan utama menegaskan bahwa integrasi Gamma.ai terbukti efektif menciptakan ekosistem pembelajaran PAI yang modern, efisien, dan adaptif tanpa mengesampingkan keaslian substansi syariat Islam. Pendidik direkomendasikan mengoptimalkan kecakapan merumuskan instruksi (prompt) secara presisi demi menjaga akurasi interpretasi hukum keagamaan.